ANALYSIS OF THE INFLUENCE OF MARKETING COSTS ON MOTOR SALES IN PT. SURACO JAYA ABADI MOTOR BRANCH GOWA - Mayang, Salmah; Asriati, Asriati; Hidayah, M (Jurnal Ekonomi Balance, 2018)
Analysis of the Effect of Marketing Costs Against PT.Suraco Jaya Abadi Motor, Gowa Branch. Marketing is one of several management activities that have an important role, because it is a direct support that has a company's activities by meeting company products with the market to satisfy customer needs, thereby increasing sales volume from the maximum sales results with low costs. This study aims to determine the effect of marketing costs on motorcycle sales at PT.Suraco Jaya Abadi Motor. The observation period began from March to April 2016 which became the object of research was PT.Suraco Jaya Abadi Motor, Gowa Branch. For data analysis descriptive analysis methods and simple regression analysis methods are used. From this study, the results obtained from the four existing promotional activities such as advertising, personal selling, sales promotion and publicity. Pt. Suraco Jaya Abadi Motor, Gowa Branch only uses two types of sales promotion and advertising activities.